Immobilization of Captive Kulans (Equus hemionus kulan) Without Using Ultrapotent Opioids - Bohner, Julia; Painer, Johanna; Bakker, Denyse; Haw, Anna Jean; Rauch, Hanna; Greunz, Eva Maria; Egner, Beate; Goeritz, Frank (Frontiers in Veterinary Science, 2022)
Etorphine is widely used in zoological medicine for the immobilization of large herbivores. All reported immobilization protocols for kulans use etorphine as the primary immobilizing agent. However, etorphine can trigger severe side effects and is highly toxic for humans, its availability is occasionally limited for use in wildlife medicine. Therefore, two different alpha-2 agonist-based protocols for the general anesthesia of kulans were investigated and compared with the standard etorphine immobilization. In total, 21 immobilizations were performed within the scope of routine husbandry management at the Serengeti-Park Hodenhagen. Kulans were darted using a ketamine–medetomidine–midazolam–butorphanol (KMMB) protocol (n = 8, treatment group (TG) 1), a tiletamine–zolazepam–medetomidine–butorphanol (TZMB) protocol (n = 7, treatment group (TG) 2), or an etorphine–acepromazine–detomidine–butorphanol (EADB) protocol (n = 6, control group). Vital parameters included heart rate, respiratory rate, arterial blood pressure (invasive), end tidal CO2 (etCO2), electromyography and core body temperature, which were all assessed every 10 min. For blood gas analysis, arterial samples were collected 15, 30, 45 and 60 min after induction. Subjective measures of quality and efficacy included quality of induction, immobilization, and recovery. Time to recumbency was longer for TG 1 (9.00 ± 1.67 min) and TG 2 (10.43 ± 1.79 min) compared to the induction times in the control group (5.33 ± 1.93 min). Treatment group protocols resulted in excellent muscle relaxation, normoxemia and normocapnia. Lower pulse rates combined with systolic arterial hypertension were detected in the alpha-2 agonist-based protocols. However, only in TZMB-immobilized kulans, sustained severe systolic arterial hypertension was observed, with significantly higher values than in the TG 1 and the normotensive control group. At 60 min following induction, medetomidine and detomidine were antagonized with atipamezole IM (5 mg/mg medetomidine or 2 mg/mg detomidine), etorphine and butorphanol with naltrexone IV (2 mg/mg butorphanol or 50 mg/mg etorphine), and midazolam and zolazepam with flumazenil IV (0.3 mg per animal). All three combinations provided smooth and rapid recoveries. To conclude, the investigated treatment protocols (KMMB and TZMB) provided a safe and efficient general anesthesia in kulans with significantly better muscle relaxation, higher respiration rates and improved arterial oxygenation compared with the immobilizations of the control group. However, the control group (EADB) showed faster recoveries. Therefore, EADB is recommended for ultra-short immobilizations (e.g., microchipping and collaring), especially with free-ranging kulans where individual recovery is uncertain, whereas the investigated treatment protocols are recommended for prolonged medical procedures on captive kulans.